SAT0119 Asymtptomatic Carotid Plaques in RA Patients is Associated with Increased HDL Function. (10th June 2014) - Rollefstad, S.; Halvorsen, B.; Skarpengland, T.; Kvien, T.K.; Provan, S.A.; Semb, A.G.P.
Abstract : Background: Reverse cholesterol transport (RCT) is a major anti atherogenic function of high density lipoprotein cholesterol (HDL-c) and has been shown to be related to disease activity in patients with rheumatoid arthritis (RA). Objectives: To evaluated if atherosclerosis affects the HDL-c function differently in RA patients compared to healthy controls. Methods: RA patients from the Oslo RA register and the European Research on Incapacitating Disease and Social Support cohorts without cardiovascular disease (CV) and not using lipid lowering agents or biologic DMARDS were included. Healthy community controls were selected by Statistics Norway. RCT was measured as plasma induced 14C-cholesterol efflux from 14C-cholesterol loaded human THP1 macrophages as previously described. 1 Apolipoprotein A1 (ApoA1) and paraoxgenase-1 (PON-1) activity was measured in serum using commercial kits. Results: Twenty RA patients, 10 with and 10 without asymptomatic carotid plaques (CP), and 10 controls were age and gender matched (p=0.09 and p=0.35, respectively). The traditional CV risk factors were comparable in RA patients with and without CP and controls; smoking: p=0.55, systolic blood pressure: p=0.77, total cholesterol: p=0.48, LDL-c p=0.31, HDL-c: p=0.89, triglycerides: p=0.85. None had diabetes. Untraditional biomarkers of CV disease as CRP, ESR and proBNP were also comparable across the 3 groups; p=0.53, p=0.86 and p=0.45, respectively. RA disease factors as disease duration, rheumatoid factor, anti-CCP and DAS-28 were comparable between RA patients with and without CP (p=0.81, p=0.34, p=0.34 and p=0.94). Efflux capacity was significantly increased in RA patients with CP compared both to controls without CP (p=0.03) and controls with CP (p=0.01). Likewise, both ApoA1 and PON-1 activity was increased in RA patients with CP compared to controls (p=0.02 and p=0.05, respectively). Further, APOA1 and PON-1 activity were comparable between RA patients without CP and controls (p=0.58 and p=0.69, respectively). Conclusions: The cholesterol efflux capacity was increased in RA patients with early atherosclerosis compared to controls, independent of HDL-c level and CRP. Our findings indicates an association between atherosclerosis and upgraded HDL-c function in patients with RA when disease activity is low, possibly as a compensatory mechanism to the atherosclerotic process. This study is hypothesis generating and larger studies are warranted to verify these findings. References: Ottestad IO, Halvorsen B, Balstad TR, Otterdal K, Borge GI, Brosstad F et al. Triglyceride-rich HDL3 from patients with familial hypercholesterolemia are less able to inhibit cytokine release or to promote cholesterol efflux. J Nutr 2006; 136(4):877-881. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5221